Model Hibrid Islamic Untuk Keberlanjutan Pesantren: Integrasi Spiritualitas dan Manajemen Modern - Nani Septiana; Siti Aimah (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to formulate and test an Islamic hybrid model to achieve sustainable development, through an in-depth analysis of the value integration mechanism, prerequisite conditions for the effectiveness of model implementation, and the determination of success indicators that measure the independence of governance and the economic sustainability of Islamic boarding schools. This model is formulated through four main components: Islamic financial governance, strengthening economic institutions, a digital accountability system, and integrative leadership, with success indicators including Islamic compliance, financial independence, institutional sustainability, and increased public trust. The study used a single qualitative case study at Darussalam Islamic Boarding School. Data collection techniques included in-depth interviews with kiai (Islamic scholars), administrators, students, and stakeholders, participant observation, and institutional document analysis. Data validity was ensured through triangulation of sources and methods, as well as prolonged engagement. The results of this study indicate that the implementation of structured tawarruq is able to maintain sharia compliance while increasing the liquidity of Islamic boarding schools, and the Waqf-Holding scheme plays a role in creating long-term financial stability. The use of digital traceability strengthens transparency and donor trust, while the Kyai-Preneur leadership pattern has proven effective in synergizing spiritual authority with managerial competence. The contribution of this study lies in the novelty of the Hybrid Islamic Model as an integrative conceptual framework for tarbiyah-good governance that is applicable in realizing the independence and sustainability of Islamic boarding schools in the modern era.